Pengaruh Variasi Ukuran Serbuk dan Waktu Tahan (Holding Time) Sintering Terhadap Kekerasan Produk Metalurgi Serbuk Paduan Limbah Alumunium (Al) Tembaga (cu) Silikon Karbida (sic) - Rizwan, Amir; Triadi, A.A. Alit; Okariawan, I Dewa Ketut; Wicaksana, Wekshi Bimo (Journal of Industrial Engineering and Innovation, 2024)
Powder metallurgy is a metalworking technology using raw materials in the form of metal powder. This research aims to determine the effect of variations in aluminum powder size and sintering resistance time on mechanical properties (hardness). The materials used in this research are aluminum (Al) which comes from leftover pieces of display cases, copper (Cu) and silicon carbide (SiC). In this research, the variations used were aluminum powder sizes, namely mesh 80 and 120, and sintering holding times, namely 60 minutes, 120 minutes and 180 minutes. The compaction and sintering process was carried out with a load of 6 tons and a temperature of 600â„ƒ degrees Celsius. The results showed that variations in aluminum powder size and sintering holding time influenced hardness. The smaller the mesh size and the longer the sintering holding time, the higher the hardness, the highest hardness occurs in the size variation of aluminum mesh powder 120 with a sintering holding time of 180 minutes 112 HRF.